The Effect of Increased Cognitive Demand on Auditory Processing Assessment - Hamlyn, Kathryn; Welldon, Katie; Clark, Benjamin; van Steenbrugge, Willem; Kapadia, Sarosh (Journal of the American Academy of Audiology, 2018)
Auditory processing (AP) is commonly regarded as the perceptual processing of auditory information in the central nervous system. However, the degree to which higher level cognitive processes are involved in AP or its disorders is contentious. Furthermore, there is little evidence regarding the effects of nonauditory cognitive processes on the various tests of AP in common clinical usage and thus on clinical diagnoses of auditory processing disorder.To determine the effects of increased cognitive demand, generated by using a dual-task paradigm, on performance on different AP tests and types of AP tests in common clinical usage. In addition, to investigate the relationship between executive function and changes in AP test performance associated with increased cognitive demand.Counterbalanced repeated measures design, with assessment of AP test performance both on its own and in a dual-task paradigm designed to increase cognitive demand.Twenty-nine young adults, with no reported hearing, learning, language or attention difficulties, English as first language, and hearing and middle-ear status within normal limits.Testing was completed within a single 90-min session. A selection of standard AP tests, representing both adaptive and nonadaptive tests, as well as tests employing difference scores, was administered. These were Competing Sentences Test, Dichotic Digits Test, Frequency Pattern Test (nonadaptive tests); and Listening in Spatialized Noise-Sentences test, conditions “same-voice, 0°”, “different-voice, 0°”, and “same-voice, 90°” (adaptive tests), from which the difference scores “talker advantage” and “spatial advantage” were also derived. Each AP test was completed on its own (alone condition), and simultaneously with a visually presented task (dual-task condition). Executive function was assessed using the phonemic subtest of the Verbal Fluency Test. Nonparametric statistical test procedures were used.All five AP measures obtained from the nonadaptive tests showed a significant performance decrement in the dual-task condition compared with the alone condition, with one exception because of a strong ceiling effect. By contrast, none of the three AP measures obtained from the adaptive tests showed a significant performance decrement in the dual-task condition. Furthermore, neither of the two AP measures based on difference scores showed a significant performance decrement, but this finding simply reflects the lack of significant decrements in the relevant raw scores. Consistent with past reports of associations between executive function and AP performance, a significant positive correlation was found between executive function scores and performance on the Dichotic Digits Test. However, there were no significant correlations between executive function scores and changes in AP test scores between alone and dual-task conditions.Performance on commonly used nonadaptive tests of AP was significantly compromised by the increased cognitive demand resulting from the dual-task paradigm. By contrast, performance on AP measures obtained by adaptive test procedures was not significantly affected. Further investigation of the resilience to increased cognitive demand of the adaptive tests used here, and other adaptive tests of AP, is warranted. Results from this study support the further development of computerized adaptive tests of AP for use in clinical test batteries.
Keywords: auditory processing; auditory processing disorder; cognitive demand; dual task; executive function